2007
DOI: 10.1302/0301-620x.89b9.18467
|View full text |Cite
|
Sign up to set email alerts
|

Is arthroscopic surgery for stabilisation of chronic shoulder instability as effective as open surgery?

Abstract: A systematic search of the literature published between January 1985 and February 2006 identified 62 studies which reported the results of arthroscopic procedures for chronic anterior shoulder instability or comparisons between arthroscopic and open surgery. These studies were classified by surgical technique and research methodology, and when appropriate, were included in a meta-analysis. The failure rate of arthroscopic shoulder stabilisation using staples or transglenoid suture techniques appeared to be sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(65 citation statements)
references
References 96 publications
2
59
1
3
Order By: Relevance
“…However, some problems have been described concerning the loss of external rotation after open surgery [35]. It is now recognized that limitation of external rotation after repair for anterior instability is a factor predisposing to capsulorrhaphy arthropathy [36].…”
Section: Long-term Results After Open Anatomical Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some problems have been described concerning the loss of external rotation after open surgery [35]. It is now recognized that limitation of external rotation after repair for anterior instability is a factor predisposing to capsulorrhaphy arthropathy [36].…”
Section: Long-term Results After Open Anatomical Proceduresmentioning
confidence: 99%
“…These two techniques have been abandoned [35]. Hobby et al [35] reviewed 19 articles who described the use of suture anchors. They had combined failure rate of 8.9%.…”
Section: Long-term Results After Arthroscopic Anatomical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…While the short-term outcome has been excellent, midterm reported results show higher rates of recurrent of instability. According to the meta-analysis by Hobby et al [ 91 ], recurrence (dislocation and subluxation) after arthroscopic Bankart repair with suture anchors varies between 0 and 29.6 %, with a mean of 8.9 %. This rate of course varies with patient factors, particularly the amount of bony defi ciency [ 25 , 71 ].…”
Section: Advantages and Pitfalls Complicationsmentioning
confidence: 99%
“…Traditionally, open repair has been the gold standard for stabilization; however, with newer methods and implants, arthroscopic repair is now preferred. Numerous studies over the past decade have shown equivalent outcomes between these two modalities [2]. …”
Section: Introductionmentioning
confidence: 99%